Analysis of Time Control Using the Earned Value Method on The Container Yard Project of the Banjarmasin Navigation and KPLP Office - Noor Riyadi; Sajiyo Sajiyo; Hanie Teki Tjendani (LPPM of NAROTAMA UNIVERSITY, 2025)
The use of an inappropriate implementation method will result in a delay in project completion time, and conversely, a properly planned implementation method will result in a time-efficient project. In the Container Yard construction project for the Navigation Office and the KPLP Office in Banjarmasin, there was a discrepancy between planned and actual progress in the 23rd week of May, where the actual progress did not reach the planned progress on site. Project execution faced obstacles and constraints, including the availability of skilled labor and the limited supply of construction materials at the project site, as well as the late arrival of materials. In addition, there were also weather factors that caused the project duration to be slightly slower than planned. The earned value method is one of the methods used to analyze a project's time performance. This method can be used to calculate the estimated time required for project completion. This underlies this research to analyze earned value to determine the extent of the project's time performance. Furthermore, the use of the earned value method in this research object is based on the need to integrate project performance measurement, which includes time and work items. The results of the study show that time performance (Schedule Performance Index) has a value of less than 1, indicating that the project performance is slower than the planned schedule. Meanwhile, the Estimate All Schedule (EAS) value shows a value of 244 days, which is 4 days longer than the planned schedule.